1985
DOI: 10.1063/1.96289
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal annealing of Si implanted GaAs for power field-effect transistors

Abstract: Rapid thermal annealing (RTA) for the electrical activation of 300-keV Si+ implants in GaAs at doses of (6–8) ×1012 cm−2 is shown to be superior to conventional annealing. Higher gateless field-effect transistor saturation currents and greater uniformities of the saturation current were measured as well as higher peak electron concentrations and mobilities. The advantages of RTA for the removal of ion implantation damage in GaAs are attributed to the heating rate being two orders of magnitude greater than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…4 were implanted with 1 • 10 ~3 cm -2 of Si 28 at 100 keV. In this figure, all the data points were obtained from the experimental results of this present study and previous literature (12,20,23,(26)(27)(28)(29)(30).…”
Section: ] Ffrpmentioning
confidence: 77%
See 1 more Smart Citation
“…4 were implanted with 1 • 10 ~3 cm -2 of Si 28 at 100 keV. In this figure, all the data points were obtained from the experimental results of this present study and previous literature (12,20,23,(26)(27)(28)(29)(30).…”
Section: ] Ffrpmentioning
confidence: 77%
“…To obtain Rp and (rrp as a function of implantation energy, E, an experimental database is generated from this study and also from earlier literature (19)(20)(21)(22)(23)(24). The results are shown in Fig.…”
Section: Activation Efficiency--the Activation Efficiency In Thismentioning
confidence: 99%
“…The results for low dose silicon implants indicate that RTA can produce doped layers suitable for device fabrication (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). By way of example, Fig.…”
Section: Silicon Implantsmentioning
confidence: 99%
“…However, not enough data are available for one to make a definitive statement about the uniformity and reproducibility of RTA (27). Kanber et al (21,22) have also observed that RTA is superior to long time furnace annealing. The results of the comparison between RTA and long time furnace annealing have to be interpreted with caution, since furnace annealing is performed normally at 850~ whereas most RTA results are at 900 ~ or 950~ and sometimes at even higher temperatures.…”
Section: Silicon Implantsmentioning
confidence: 99%
See 1 more Smart Citation